PENGGUNAAN MEDIA APLIKASI VIRUS AUGMENTED REALITY (VAR) UNTUK MENINGKATKAN DISPOSISI KREATIF DAN KETERAMPILAN BERPIKIR KREATIF SISWA SMA - Putri Sri Rizki Parani; AA Sukarso; Mahrus Mahrus; Khairuddin Khairuddin (Postgraduate, University of Mataram, 2023)
This study aims to reveal the effect of using the Augmented Reality (VAR) Virus Application in arousing the creative dispositions and creative thinking skills of high school students. The research was conducted on 118 class X students at a public high school in Mataram in biology lessons on viruses. The research was conducted using an experimental method pretest and posttest control group design. The experimental class group of students got learning by using the VAR application and the control group using the power point application (ppt). Both classes received pretest and posttest by filling out creative disposition questionnaires and tests of creative thinking skills before and after the intervention. Research data in the form of quantitative data, both creative disposition and creative thinking skills, were tested and analyzed using the N-gain test and difference test. The results of the study revealed that the VAR application aroused students' creative dispositions in the medium category (N-gain 0.41) for the experimental class (VAR application) and in the low category (N-gain 0.23) for the control class (ppt application), both statistically significantly different. The creative thinking skills of VAR class students increased in the moderate improvement category (N-gain 0.32) and in the low category ppt class (N-gain 0.09), both of which also showed significant differences. The conclusion of this study is that the use of the VAR application has the potential to be used as a learning aid for Virus material and is recommended to be suitable for stimulating the growth of creative thinking skills